2015
DOI: 10.1038/cddis.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia restores apoptosis induced by death receptors through aggregation-induced c-FLIP cytosolic depletion

Abstract: TRAIL is involved in immune tumor surveillance and is considered a promising anti-cancer agent owing to its limited side effects on healthy cells. However, some cancer cells display resistance, or become resistant to TRAIL-induced cell death. Hyperthermia can enhance sensitivity to TRAIL-induced cell death in various resistant cancer cell lines, including lung, breast, colon or prostate carcinomas. Mild heat shock treatment has been proposed to restore Fas ligand or TRAIL-induced apoptosis through c-FLIP degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…We have already established the magnetocalorimetric properties of coated (Hai et al, ) and uncoated (Hanini et al, ) polyol‐made iron oxide NPs and their ability to induce malignant cell apoptosis by hyperthermia, opening up synergetic therapeutic opportunities. Indeed, a local rise of temperature under an applied AC magnetic field can sensitize tumor cells to TRAIL‐induced apoptosis (Morle et al, ; Moulin and Arrigo, ; Moulin et al, ; Yoo et al, ) as it can compensate the lack of efficiency of TRAIL in certain resistant cells (Song et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have already established the magnetocalorimetric properties of coated (Hai et al, ) and uncoated (Hanini et al, ) polyol‐made iron oxide NPs and their ability to induce malignant cell apoptosis by hyperthermia, opening up synergetic therapeutic opportunities. Indeed, a local rise of temperature under an applied AC magnetic field can sensitize tumor cells to TRAIL‐induced apoptosis (Morle et al, ; Moulin and Arrigo, ; Moulin et al, ; Yoo et al, ) as it can compensate the lack of efficiency of TRAIL in certain resistant cells (Song et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that L-asparaginase affects protein synthesis, it is likely that the level of proteins with a short half-life, such as Mcl-1 [28, 29], c-FLIP [30, 31] or survivin [32] are decreased by L-asparaginase which in turn increases TRAIL-mediated apoptosis. Consistently, our findings showed that L-asparaginase broadly sensitized glioblastoma cells to TRAIL-mediated apoptosis in a synergistic fashion.…”
Section: Discussionmentioning
confidence: 99%
“…When bound to specific DR4 or DR5, TRAIL homotrimers induce multimerization of these receptors, allowing subsequent recruitment of intracellular proteins through homotypic interactions, thanks to a short domain composed of 80 amino acids called the Death Domain (DD). This cascade of events lead to the formation of the Death‐Inducing Signaling Complex (DISC), at the membrane level, a macromolecular complex, the composition of which determines the fate of the cell (Morlé et al, ), undergoing or not apoptosis (J.L. ; Bodmer et al, 2000; LeBlanc et al, ; Shirley et al, ).…”
Section: Introductionmentioning
confidence: 99%